The Implementation of Collaborative Learning Models in Improving Speaking Skills - Putri Hana Pebriana; Widya Puspita Sari; Ulfa Zahera; Sindy Viza Fhahira; Wulandari Wulandari; Salwa Nadhifah; Asna Lia Clarisa (The Future of Education Journal, 2026)
Speaking skills are an essential competence in language learning, supporting effective communication and active student participation. This study aims to analyze the implementation of the collaborative learning model to enhance students’ speaking skills. A Systematic Literature Review (SLR) was conducted to evaluate previous studies on collaborative strategies, discussion techniques, and group activities in the context of language learning. The findings indicate that collaborative models, such as Think-Pair-Share, Jigsaw, and Role-Play, effectively improve students’ confidence, argumentation skills, fluency, and active engagement in learning. The implementation of this model also promotes social interaction, teamwork, and peer reflection. However, challenges include uneven group management, differences in student abilities, and teacher readiness to facilitate collaborative learning. This study recommends structured collaborative strategies, clear role assignments, and pedagogical training for teachers to maximize the effectiveness of speaking skill development in the classroom.